Differentiation of chromoplasts and other plastids in plants - Sadali, N; Sowden, R; Ling, Q; Jarvis, R (Elsevier, 2019)
Plant cells are characterized by a unique group of interconvertible organelles called plastids, which are descended from prokaryotic endosymbionts. The most studied plastid type is the chloroplast, which carries out the ancestral plastid function of photosynthesis. During the course of evolution, plastid activities were increasingly integrated with cellular metabolism and functions, and plant developmental processes, and this led to the creation of new types of non-photosynthetic plastids. These include the chromoplast, a carotenoid-rich organelle typically found in flowers and fruits. Here, we provide an introduction to non-photosynthetic plastids, and then review the structures and functions of chromoplasts in detail. The role of chromoplast differentiation in fruit ripening in particular is explored, and the factors that govern plastid development are examined, including hormonal regulation, gene expression, and plastid protein import. In the latter process, nucleus-encoded preproteins must pass through two successive protein translocons in the outer and inner envelope membranes of the plastid; these are known as TOC and TIC (translocon at the outer/inner chloroplast envelope), respectively. The discovery of SP1 (suppressor of ppi1 locus1), which encodes a RING-type ubiquitin E3 ligase localized in the plastid outer envelope membrane, revealed that plastid protein import is regulated through the selective targeting of TOC complexes for degradation by the ubiquitin-proteasome system. This suggests the possibility of engineering plastid protein import in novel crop improvement strategies.